Detection and molecular analysis of Pseudorabies virus from free-ranging Italian wolves (Canis lupus italicus) in Italy - a case report - Moreno, Ana; Musto, Carmela; Gobbi, Marco; Maioli, Giulia; Menchetti, Marika; Trogu, Tiziana; Paniccià, Marta; Lavazza, Antonio; Delogu, Mauro (BMC veterinary research, 2024)
The only natural hosts of Pseudorabies virus (PRV) are members of the family Suidae (Sus scrofa scrofa). In mammals, the infection is usually fatal and typically causes serious neurologic disease. This study describes four Aujeszky's disease cases in free-ranging Italian wolves (Canis lupus italicus). In Italy, the wolf is a strictly protected species and is in demographic expansion. Three wolves (Wolf A, B, and C) were found in a regional park in Northern Italy, and one (Wolf D) was found in Central Italy. Wolf A and D were alive at the time of the finding and exhibited a fatal infection with epileptic seizures and dyspnoea, dying after a few hours. Wolf B presented scratching lesions under the chin and a detachment of the right earlobe, whilst Wolf C was partially eaten. The wolves showed hepatic congestion, diffuse enteritis, moderate pericardial effusion, severe bilateral pneumonia, and diffuse hyperaemia in the brain. The diagnostic examinations included virological analyses and detection of toxic molecules able to cause serious neurological signs. All four wolves tested positive for pseudorabies virus (PrV). The analysed sequences were placed in Italian clade 1, which is divided into two subclades, "a" and "b". The sequences of Wolf A, B, and C were closely related to other Italian sequences in the subclade b, originally obtained from wild boars and hunting dogs. The sequence from Wolf D was located within the same clade and was closely related to the French hunting dog sequences belonging to group 4. Results showed the presence of PrV strains currently circulating in wild boars and free-ranging Italian wolves. The genetic characterisation of the PrV UL44 sequences from the four wolves confirmed the close relationship with the sequences from wild boars and hunting dogs. This fact supports a possible epidemiological link with the high PrV presence in wild boars and the possibility of infection in wolves through consumption of infected wild boar carcasses or indirect transmission. To the best of our knowledge, this study is the first detection of Pseudorabies virus in free-ranging Italian wolves in northern and central Italy.